INTERFAITH COMMUNICATION DALAM DAKWAH: ANALISIS DAKWAH BRO SHAH KIRIT, GLOBAL UNITY NETWORK - Rachima, Amanda Puspa; Sansayto, Tistigar; Al Hakimah, Henin Justitia; Az Zuhroh, Talia; Alexandra, Silviana Dewi; Aisyah, Siti Nur (UIN Sumatera Utara Medan, 2026)
This study examines the dialogical da'wah model of Bro Shah Kirit and the role of the Global Unity Network in promoting interfaith communication in Malaysia. The research is grounded in the growing need for approaches to Islamic preaching that respond peacefully and intelligently to religious diversity in a multicultural society. This study employs a qualitative approach with a field research method, encompassing direct observation in interfaith forums, analysis of sermons and public recordings, as well as brief interviews with speakers and participants involved in the activities. The findings reveal that Bro Shah emphasizes respectful dialogue, critical engagement with religious texts, logical reasoning, and appreciation for other faith traditions as the foundation of his communication style. The Global Unity Network functions as a platform for interfaith education through seminars, workshops, and public discussions. This study concludes that the dialogical da'wah approach serves as an effective strategy to foster social harmony, mutual understanding, and inclusive religious engagement in plural societies.